FYSIKKENS ERKENDELSESLÆRE OG MENNESKE-KULTURERNE: Med efterskrift af Jørgen Kalckar - Bohr, Niels; Kalckar, Jørgen (Tidsskriftet Antropologi, 1997)
Niels Bohr: Physics’ Epistemology and Human Cultures The article is a reprint of the talk given by the famous physicist when he addressed the International Congress of Anthropology and Ethnology at Kronborg, Elsinore, in August Niels Bohr’s new theory of quantum physics gave rise to the concept of complementarity, and the Elsinore leeture was the first occasion on which he publically debated questions regarding evolution and the mutual interplay of cultures. The topic derives from Bohr’s reflections on the complementarity of instinet and reason. Furthermore, these thoughts were related to the issue of nature versus nurture, on which Bohr unambiguously sided with the latter. The Elsinore leeture is more provocative and a little less taetful than Bohr’s usual style, and might be considered as a reaction to racist ideology so prevalent in the 1930s. It is worth noting, however, that these issues are being debated in the 1990s. The wider relevance of the concept of complementarity and its applicability to disciplines outside the natural Sciences occupied Bohr throughout his life.